Evaluation of the Immunochromatographic NG-Test Carba 5, RESIST-5 O.O.K.N.V., and IMP K-SeT for Rapid Detection of KPC-, NDM-, IMP-, VIM-type, and OXA-48-like Carbapenemase Among Enterobacterales - Han, Renru; Guo, Yan; Peng, Mingjia; Shi, Qingyu; Wu, Shi; Yang, Yang; Zheng, Yonggui; Yin, Dandan; Hu, Fupin (Frontiers in Microbiology, 2021)
Background: Enterobacterales are the most common pathogens for nosocomial infections. The emergence and spread of KPC, NDM, and OXA-48-like carbapenemase-producing Enterobacterales with their extensively drug resistant characteristics have posed great threats to public health. This study aimed to evaluate the performance of NG-test Carba 5, RESIST-5 plus IMP K-SeT for rapid detection of five carbapenemases (KPC, NDM, VIM, IMP, and OXA-48-like) among Enterobacterales. Methods: 186 carbapenem-resistant Enterobacterales clinical isolates and 29 reference strains were used in this study. Carbapenemase genes were confirmed by PCR and DNA sequencing. The sensitivities and specificities of these assays were calculated utilizing the VassarStats software. Results: For clinical isolates, the NG-test Carba 5 detected KPC, NDM, OXA-48-like, IMP, and VIM in less than 15 minutes with the sensitivity and specificity of 100% and 100%, respectively. The RESIST-5 detected KPC, NDM, OXA-48-like and VIM with the sensitivity and specificity of 99.4% and 100%. The IMP K-SeT detected all of IMP-producers (6/6). For reference strains, the sensitivity and specificity of NG-test Carba 5, RESIST-5 plus IMP K-SeT were 100% and 100%, respectively. Conclusions: As efficient, rapid and convenient diagnostic methods, NG-test Carba 5, RESIST-5 plus IMP K-SeT could help to simplify the complex routine workflow for detecting carbapenemases. Rapid and accurate identification of carbapenemase is of significance for both epidemiological and infection control purposes.